2005
DOI: 10.1161/01.cir.0000160353.27927.70
|View full text |Cite
|
Sign up to set email alerts
|

25-Hydroxyvitamin D 3 -1α-Hydroxylase Is Expressed in Human Vascular Smooth Muscle Cells and Is Upregulated by Parathyroid Hormone and Estrogenic Compounds

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
236
0
8

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 340 publications
(253 citation statements)
references
References 45 publications
3
236
0
8
Order By: Relevance
“…In fact, the lack of evidence from randomized, controlled trials measuring vitamin D intake and incident disease, rather than serum levels of 25 (68), and/or regulation of the renin/ angiotensin pathway (69), which may not be reflected in the arterial phenotypes measured. The effects of vitamin D on vascular smooth muscle cells are complex and are modulated by other hormones, such as PTH and estrogenic compounds, which upregulate 1 a-hydroxylase in these cells (63,70,71). Our findings in children are in line with the very recent findings by Richart et al (72), who showed that in a general population cIMT increased with higher PTH/25(OH)D 3 ratio and higher PTH but was not significantly associated with 25(OH)D 3 .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the lack of evidence from randomized, controlled trials measuring vitamin D intake and incident disease, rather than serum levels of 25 (68), and/or regulation of the renin/ angiotensin pathway (69), which may not be reflected in the arterial phenotypes measured. The effects of vitamin D on vascular smooth muscle cells are complex and are modulated by other hormones, such as PTH and estrogenic compounds, which upregulate 1 a-hydroxylase in these cells (63,70,71). Our findings in children are in line with the very recent findings by Richart et al (72), who showed that in a general population cIMT increased with higher PTH/25(OH)D 3 ratio and higher PTH but was not significantly associated with 25(OH)D 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this observation may most likely reflect 25D's advantageous characteristics as a biomarker (a more reproducible assay and a longer half-life) when compared with 1,25D, thus enabling more accurate measurement of exposure over time (6). In addition, it is possible that in CKD patients with markedly deficient renal production of 1,25D, the maintenance of adequate reserves of 25D may be especially important in maintaining VDR activation in cells that rely on autocrine pathways; this is the case for cultured human vascular smooth muscle cells (which have been shown to express functional 1-␣ hydroxylase [35]) and cultured human endothelial cells (in which the expression of the mRNA and protein for 1-␣ hydroxylase have been demonstrated [36]). It should be noted that the 25D assay used in the present study measures both ergocalciferol (D 2 ) and cholecalciferol (D 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Somjen et al (9) were the first to report an enzymatically active 25(OH)D1 ␣-hydroxylase system in human vascular smooth muscle cells, which could be upregulated by parathyroid hormone (PTH) and inhibited by exogenous vitamin D. Emerging experimental data demonstrate important physiologic effects of vitamin D on factors that are protective for vascular health (10).…”
Section: Vascular Effectsmentioning
confidence: 99%